Spontaneous cervical artery dissection is associated with a distinct peripheral immune cell signature - Carolin Beuker; Andreas Schulte-Mecklenbeck; Timo Wirth; Ilka Kleffner; Christian Thomas; Daniel Strunk; Antje Schmidt-Pogoda; Catharina C. Gross; Luisa Klotz; Jens Minnerup (PLoS ONE, 2026)
Objectives Despite being a major cause of ischemic stroke in young adults, the biological underpinnings of cervical artery dissection (CeAD) remain poorly defined. Recent data implicate immune activation as a potential contributor. We aimed to determine whether patients with CeAD display a distinct peripheral immune signature, which may provide insights into pathogenic inflammatory processes. Methods Peripheral blood mononuclear cells (PBMCs) from patients with spontaneous CeAD (n = 7 without and n = 11 with ischemic stroke) and ten age-matched healthy controls were analyzed via multi-color flow cytometry. Immune cell composition and activation markers were assessed, and sparse partial least squares discriminant analysis (sPLS-DA) was employed to identify CeAD-associated immune features. A secondary comparison with ischemic stroke controls was included to assess the specificity of identified immune alterations. Results Compared to healthy controls, CeAD patients displayed increased frequencies of CD4 ⁺ T cells and decreased natural killer T (NKT) cells. sPLS-DA demonstrated clear separation of CeAD and control immune profiles, driven by increased CD28 expression on naïve CD8 ⁺ T cells, NKp46 on NK cells, and IL-2Rα (CD25) on myeloid dendritic cells (mDC2). Elevated granzyme K in naïve CD8 ⁺ T cells indicated enhanced cytotoxic potential, while regulatory T cells were diminished. These alterations were largely preserved when compared to ischemic stroke controls, suggesting CeAD-specific immune activation. No microbial pathogens were detected by untargeted metagenomic sequencing. Discussion CeAD is associated with a distinct peripheral immune signature characterized by enhanced cytotoxic activity and reduced regulatory features. These alterations may reflect a post-infectious autoimmune mechanism triggering CeAD or a secondary immune-inflammatory response to vascular injury. Larger, longitudinal studies are needed to clarify causality and assess whether immune modulation could serve as a therapeutic target in CeAD.